Pemetaan Literatur tentang Walisongo di Perpustakaan UIN Walisongo dan Pemanfaatannya oleh Pemustaka - Miswan, Miswan; Ulumi, Bahrul; Akyas, Gibran (Syarif Hidayatullah State Islamic University of Jakarta, 2023)
This study examines the development and mapping of printed literatures on “Walisongo”. The study aims to reveal the strength of the collection concerning Walisongo among other collections in the UIN Walisongo library. The results showed that the query